Molecular Hydrogen: A Promising Adjunctive Strategy for the Treatment of the COVID-19 - Li, Yingning; Wang, Zhen; Lian, Naqi; Wang, Yuzun; Zheng, Weiqiang; Xie, Keliang (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) is an acute respiratory disease caused by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has no specific and effective treatment. The pathophysiological process of the COVID-19 is an excessive inflammatory response after an organism infects with a virus. Inflammatory storms play an important role in the development of the COVID-19. A large number of studies have confirmed that hydrogen has a therapeutic effect on many diseases via inhibiting excessive inflammatory cells and factors. Recently, a study led by the Academician Zhong Nanshan in China on the treatment of the patients with the COVID-19 by inhalation of a mixed gas composed of hydrogen and oxygen has attracted widespread international attention and hydrogen therapy has also been included in a new treatment plan for the COVID-19 in China. This study mainly describes the mechanism of occurrence of the COVID-19, summarizes the therapeutic effects and underlying mechanisms of hydrogen on the critical disease, and analyzes the feasibility and potential therapeutic targets of hydrogen for the treatment of the COVID-19.